Evaluasi Kinerja Konsultan Pengawas Pada Proyek Jalan Dan Jembatan Di Kabupaten Manggarai - Jaya, Marselina Eka; Gado, Alfridus (TEKNOSIAR, 2021)
n carrying out work in the field of roads and bridges at the Manggarai Regency Public Works Agency forFiscal Year 2020, it is not following contract documents and work specifications, including measurementresults errors, not properly checking the origin and quality of materials, and limited inspection personnelboth in terms of quantity and qualifications. The objectives of this study include: determining theperformance of the Supervisory Consultant and determining the influence of the variable factors ofUnderstanding Contract Documents, Understanding of Quality of Road Construction Implementation,Monitoring of Road Construction Work Methods, Monitoring of Measurement Results, Use of Equipment,Monitoring of Time and Progress of Road Works, Supervision of Application of Study DocumentsEnvironment, Preparation of Meeting Materials, Reporting on Road Work Progress Activities and theHandover Process of Work Results. The method used in this research is descriptive quantitative. Data wereobtained through interviews with PPK and questionnaires distributed to 20 respondents: Contractors,Inspectors, Quality Control, and Site Engineers. The results of the analysis are the performance ofsupervisory consultants on road and bridge projects in Manggarai Regency in the 2020 fiscal year with avalue of 3.35 and the value of R Square on the coefficient of determination of 0.996 and the most dominantfactor is Supervision of the Implementation of Environmental Study Documents with a regression coefficientvalue of 1,443.